Body Mass Index (BMI) as a predictive factor of thoracic insufficiency syndrome in adolescent idiopathic scoliosis (AIS) - Johari, Joehaimey; Sharifudin, Mohd Ariff; Ab Rahman, Azriani; Omar, Ahmad Sabri (2014)
Among the reported complications of scoliosis is restrictive lung disease. Resting metabolic rate is increased when the pulmonary function is impaired. Reduction in patients’ body mass index (BMI) may be an important indicator of thoracic insufficiency syndrome. The objective of this retrospective study was to determine the correlation between spinal deformity, pulmonary function and BMI. All patients with adolescent idiopathic scoliosis (AIS) aged between 13 to 24 years, confirmed cases of AIS, and admitted at Hospital Raja Perempuan Zainab II for surgical interventions from year 2000 to 2013 were selected. Spinal deformity were determined by measuring the spinal curve angle using the Cobb angle on anterior-posterior radiographs. Pre-operative pulmonary function were evaluated using the forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1). Pearson correlation was performed to analyse the correlation between spinal deformity and pulmonary function with BMI. Thirty-eight patients were recruited. The mean age of patients was 16.7 years (SD = 6.04). Significant positive fair correlations between BMI and pre-operative FEV1 (p=0.009; r=0.417), and FVC (p=0.018; r=0.38) were observed. However, the correlation between BMI and Cobb angle was not significant (p=0.363). In conclusion, BMI was affected by poor lung function in AIS patients and can be used as a predictive factor of thoracic insufficiency syndrome.